Anti-feminist backlash: The role of system justification in the rejection of feminism. (July 2014) - Yeung, Amy W. Y.; Kay, Aaron C.; Peach, Jennifer M.
System justification theory (SJT) posits that people are motivated to believe that the social system they live in is fair, desirable, and how it should be, especially in contexts that heighten the system justification motive. Past researchers have suggested that opposition to feminists may be motivated by the threat that feminism presents to the legitimacy of the status quo, but this hypothesis has not been tested empirically. In this article, we present three studies that directly test the idea that antifeminist backlash can be motivated by system justification. Studies 1 and 2 experimentally manipulated the SJ motive and a female target's feminist identification (feminist vs. nonfeminist). Study 3 tested the hypothesis by measuring participants' SJ motivation via an individual difference measure. Participants disagreed more with identical statements about gender issues made by the feminist target than the nonfeminist target, but only when the system justification motive was heightened (Study 2) or chronically high (Study 3).